4D Imaging of Mineral Dissolution in Porous Carbonado Diamond: Implications for Acid Digestion and XCT Measurement of Porosity and Material Properties - Eckley, Scott A.; Ketcham, Richard A. (Frontiers in Earth Science, 2019)
Dissolution and leaching are difficult processes to observe with combined temporal and spatial context, particularly when dissolving material within a nonreactive pore network. X-ray computed tomography (XCT) is a uniquely suited technique for observing dissolution in situ, and extracting quantitative data on pore networks and the material in them in 3D. We XCT imaged two samples of porous diamond (carbonado) during a sequential acid leaching procedure designed to remove a diverse assemblage of pore-filling minerals. This experiment allowed us to not only observe mineral dissolution in 3D, but also test various approaches to measuring porosity. We found that methods based on quantitative interpretation of CT numbers as partial porosity give more accurate results than purely binary segmentation, and that attempts to segment the pore network using visual criteria were scattered and unreliable. We identified differences in mineral inclusions and pore network topology between carbonado samples based on dissimilar dissolution styles and rates. We were also able to observe the formation of insoluble fluorides during acid digestion, which can drastically affect yields for geochemical measurements of certain elements, most importantly REEs, U, Th, and Pb. We found that image quality is unexpectedly locally affected by material properties, with filled pores measurably blurrier than empty ones. Such local variation in point-spread function is important when segmenting any object in XCT for the purposes of quantification. Finally, we demonstrate that by comparing mass and X-ray attenuation loss it is possible to estimate the relative heavy-metal content of the leached material.